Spiritual Authority and Political Adaptation: Sufism in Indonesia's New Order Era (1966–1998) - Muhammad Husein (Jurnal Riset Multidisiplin Edukasi, 2026)
This article examines the complex and dynamic relationship between Sufism and state power during Indonesia's New Order period. It argues against the prevailing notion that Sufi orders (tarekat) were apolitical or merely retreatist spiritual movements. Instead, the study demonstrates how various tarekat, particularly the Qadiriyya wa Naqsyabandiyya (TQN), underwent significant processes of rationalization, bureaucratization, and political engagement. Through a historical-sociological analysis of primary and secondary literature, the article traces the transformation of Sufism from a primarily rural, charismatic-based tradition into a modern socio-political force. Key findings reveal a pattern of state co-optation, where the regime sought to harness the mass following of the tarekat for developmental legitimacy and political stability. Concurrently, Sufi leaders navigated the political landscape with diverse strategies ranging from active collaboration with the ruling Golkar party, to opposition through Islamic parties, to deliberate neutrality. This period also witnessed the rise of charismatic "living saints" (wali) whose spiritual authority was leveraged for political mobilization. Ultimately, the New Order era was not a period of Sufi decline but one of profound adaptation, where mystical Islam actively negotiated its place within an authoritarian modernizing state, leaving a lasting legacy on Indonesia's religious and political topography.